Study on multi-cycle coupling mechanism of hypersonic precooled combined cycle engine. (25th February 2018) - Dong, Pengcheng; Tang, Hailong; Chen, Min
Highlights: HPCCE contains precooling method, dual-mode feature and multi-cycle coupling mechanism. Large-scale frequent energy exchange enables HPCCE to utilize energy in high speed intake air. Core compressor connects cycles which should efficiently work in a wide pressure ratio range (4.0–10.0). Engine design reflects compromises between hypersonic and subsonic work conditions. Over-high coolant flow rate shadows benefits. Innovation of flow path and its detail discussion are needed. Abstract: Propulsion system is a crucial issue of hypersonic civil aviation. Precooled engine shows attractive advantages in high flight Mach numbers, and the hypersonic precooled combined cycle engine (HPCCE) is one of the most potential plans. Multi-cycle coupling is the most remarkable feature of HPCCE, reflected by the large-scale frequent energy exchange among subsystems, i.e. opened cycle, closed cycle and propellant system, and the interaction between the designs for different working conditions. The mechanism is studied through engine cycle analysis with enthalpy-entropy relations. Quantitative discussion on major design parameters based on a component level simulation model shows the trends of inter-impact among subsystems and parameters, and sketches the multi-cycle mechanism and energy transfer relations in detail. Vital issues that should be emphasized through the design process are pointed out.